2019
DOI: 10.2196/13658
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and HIV Screening Uptake Among Deaf Adults in the United States: Cross-Sectional Survey Study

Abstract: Background About 46% of US adults obtain recommended HIV screening at least once during their lifetime. There is little knowledge of screening rates among deaf and hard-of-hearing adults who primarily use American Sign Language (ASL), or of social media as a potentially efficacious route for HIV prevention outreach, despite lower HIV/AIDS-specific health literacy and potentially higher HIV seropositivity rates than hearing peers. Objective We investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Although both education and physical distancing awareness strongly predicted perceptions of the effectiveness of physical distancing, this study did not find evidence for the contribution of age, gender, and race to the development of appropriate perception of physical distancing effectiveness. This finding is consistent with research studies that reported a connection between more years of education and a greater level of health-related awareness or screening uptake [ 6 - 8 ]. Our study also showed that DHH people who have a college degree, as well as knowledge of the effectiveness of physical distancing, were much more likely to believe that an infected person without symptoms is contagious compared to DHH people who did not have a college degree and demonstrated low knowledge of the effectiveness of physical distancing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although both education and physical distancing awareness strongly predicted perceptions of the effectiveness of physical distancing, this study did not find evidence for the contribution of age, gender, and race to the development of appropriate perception of physical distancing effectiveness. This finding is consistent with research studies that reported a connection between more years of education and a greater level of health-related awareness or screening uptake [ 6 - 8 ]. Our study also showed that DHH people who have a college degree, as well as knowledge of the effectiveness of physical distancing, were much more likely to believe that an infected person without symptoms is contagious compared to DHH people who did not have a college degree and demonstrated low knowledge of the effectiveness of physical distancing.…”
Section: Discussionsupporting
confidence: 92%
“…However, most DHH ASL speakers, particularly DHH people with a high school degree or less, depend on information presented in ASL in videos as their go-to source for health information, with Facebook being the most often used source [ 5 ]. Previous studies have shown that DHH people with a high school degree or less have lower human papillomavirus knowledge, genetic testing awareness, and HIV screening uptake, all of which can be remedied with greater accessibility of pertinent information in ASL [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although both education and physical distancing awareness strongly predicted perceptions of the effectiveness of physical distancing, this study did not find evidence for the contribution of age, gender, and race to the development of appropriate perception of physical distancing effectiveness. This finding is consistent with research studies that reported a connection between more years of education and a greater level of health-related awareness or screening uptake [6][7][8]. Our study also showed that DHH people who have a college degree, as well as knowledge of the effectiveness of physical distancing, were much more likely to believe that an infected person without symptoms is contagious compared to DHH people who did not have a college degree and The lower knowledge of physical distancing and COVID-19 among DHH people who do not have a college degree may be in part explained by inadequate, inaccessible, or misleading information presented in ASL on social media.…”
Section: Principal Findingssupporting
confidence: 91%
“…However, most DHH ASL speakers, particularly DHH people with a high school degree or less, depend on information presented in ASL in videos as their go-to source for health information, with Facebook being the most often used source [5]. Previous studies have shown that DHH people with a high school degree or less have lower human papillomavirus knowledge, genetic testing awareness, and HIV screening uptake, all of which can be remedied with greater accessibility of pertinent information in ASL [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted by our participant responses, this population requires more HIV and other health resources in ASL and access to health care interpreters that are adequately trained to work with Deaf older PLWH. Recent research suggests social media may be an effective means of promoting HIV education among Deaf adult ASL users (Argenyi & Kushalnagar, 2019), whereas health care facilities may consider using or adopting Deaf peer educator programs, which have been successful internationally (He et al, 2020).…”
Section: Discussionmentioning
confidence: 99%